VENTRICULAR ARRHYTHMIAS IN YOUNG ATHLETES: ARE THERE ANY POSSIBLE PREDICTORS?. (June 2018) - Toncelli, L.; Chiostri, M.; Bartolini, A.; Ciullini, G.; Vono, M.; Tosi, B.; Modesti, P.A.; Galanti, G.
Abstract : Objective: Objective: Long-term outcomes of frequent and/or complex ventricular arrhythmias in apparently healthy athletes are still controversial. Ventricular ectopy in young athletes often originates from the right ventricle. Arrhythmias can be a clinical expression of an initial cardiovascular disease that may not be easily detected in the growing age. Design and method: Design and method:The present study was designed to investigate the right ventricle morphology and function trough echocardiography in young athletes with ventricular arrhythmias originating from right ventricle. 265 young athletes were recruited, aged 9 to 18 years, 158 male and 107 females. 97 of them presented frequent and/or complex ventricular arrhythmias at baseline EKG which did not disappear nor decrease during exercise test (group A) while 168 of them had no arrhythmias (group B). All athletes underwent echocardiogram focused on right ventricle, according to the American Society of Echocardiography's guidelines. A multivariate logistic regression analysis was performed to identify possible adjusted predictors of arrhythmias. The coefficients obtained were used to develop a scoring system to calculate the risk of arrhythmia. Results: Results: No sex differences were found. All echocardiographic parameters were between the normal range though the athletes with arrhythmias were older, heavier and taller. Group A presented different right ventricle systolic function indexes, namely a lower TAPSE, a higher MPI index and more positive values of strain; moreover, they had lower right ventricle longitudinal dimensions and higher end diastolic area (both absolute and indexed for subject's height). The likelihood of arrhythmia increased with age, with the decrease in systolic function parameters and with a glossier aspect of right ventricle. This score seems reliable in predicting the development of frequent and complex extrasistolia in young athletes (65% sensitivity, 86% specificity Conclusions: Conclusions: Athletes with a score value of 250 or more, should be more closely followed with EKG Holter and accurate echocardiographic study of right ventricle to detect early signs of cardiac disease.